Contribución del estado de Zacatecas (México) a la conservación de la riqueza florística del Desierto Chihuahuense - de Jesús Balleza, José; Villaseñor, José Luis (Instituto de Ecología, A.C., 2011)
The Chihuahuan Desert (DCH) is the largest and floristically richest arid zone in northern Mexico. The DCH includes territories of seven Mexican states, including Zacatecas and San Luis Potosí where its southern limit is located. Zacatecas harbors 46% of the vascular flora recorded in the DCH and the Asteraceae family is an important component of such richness, both throughout the DCH as a whole and within its Zacatecan portion. Unfortunately, Zacatecas has not been adequately considered in the different conservation strategies proposed to protect the floristic richness of the DCH. In this paper we describe a selection of sites in Zacatecas that are important for the conservation of floristic richness, using 198 species of Asteraceae as a surrogate of the entire flora and dividing the fraction of the DCH in the state into 26 squares of 30 minutes latitude and longitude. The sites were identified by means of an iterative method, the results of which indicate the necessity of protecting 18 squares to ensure the conservation of the totality of species. The location of the most important squares identified, as well as the role that Zacatecas may potentially play in the conservation of the biodiversity of the DCH are discussed.